The New Penglipurlara: spoken word poetry and the revival of the storyteller in Malaysian literature in English - Baharudin, Nur Sheena (2021)
The New Penglipurlara is a pragmatic and eclectic approach to the field of spoken word poetry. It identifies and explores the phenomenon of performing personal stories as reflected in its increasing visibility in Malaysia over the past decade. This proliferation of events and sub-communities of contemporary storytellers appear to be reflected not only in critical discourses including narratology, performance studies and the postcolonial scholars’ interest in oral tradition, but also in areas such as cognitive science. Despite this, spoken word poets and their works remain relatively absent in literary criticism and theory, an omission that may have arisen in part due to a fixation on the dichotomy of the oral and the text, rooted in an Eurocentric mindset that regards literacy as a defining feature of civilization and orality as an archive of its primitive predecessors. This study aims to address this under-explored area by plotting a local literary history of performing stories beginning from the traditional Malay storyteller known as the penglipurlara to a selected group of contemporary, urban spoken word poets based in Kuala Lumpur who actively contributed to the artform from 2007-2017. It argues that not only do these two groups of storytellers share more similarities than differences, the popularity of spoken word poetry in the last 10 years is evident of the country’s oral/aural past and its return to the verbal art as a mode of communication in Malaysian society. Drawing largely on methodologies informed by folklorists, postcolonial and performance theorists, it investigates how spoken word poets use the medium as a way to challenge established narratives and engage with the personal and the concerns of their society at large. Through an interdisciplinary reading of spoken word poems, observations and interviews, this study reveals that spoken word poetry functions as an emergent site of complex and multilayered identities and meaning making. It also shows how this new generation of oral storytellers offers researchers and practitioners valuable tools and resources with which to navigate and re-map the fields of contemporary Malaysian literary studies.